Complementary and Alternative Medicine Provider Knowledge Discourse on Holistic Health - Agarwal, Vinita (Frontiers in Communication, 2018)
Complementary and alternative medicine (CAM) promises a wide array of therapies employed increasingly by consumers for disease prevention and health promotion. Despite this increasing use, however, CAM and biomedical paradigms are often not combined effectively in the US. The lack of coordination negatively impacts several aspects of patient care including CAM and biomedical provider-patient relationships and the practice of integrative medicine. The goal of this study is to understand how CAM providers position their knowledge and practice of holistic health within the healthcare landscape in the US. In-depth interviews with CAM providers (N=17) sampled from practices in the mid-Atlantic region of the US were analyzed for provider descriptions of holistic health. Discourse analysis of CAM provider interviews identifies the three themes employed by CAM providers to describe holistic health as comprising the: (a) epistemologies of legitimization and identity, (b) epistemologies of sense and intuition, and (c) epistemologies of environment and community. The three epistemologies define holistic health by organizing diverse knowledge foundations through reconciling and integrating differences, including diverse modes of evidence such as non-empirical forms of whole body experiences, and privileging the relational praxis through integrating the individual’s biological and sociocultural environment. The epistemologies illuminate how CAM knowledge and practice is positioned as alternative within the sociocultural context of the participants and reflect CAM providers’ challenges in carving out a distinct knowledge space reflecting their professional identity. CAM providers’ discourse encompasses the ontological and experiential-relational praxis to foreground health as a mutually constitutive, ongoing process of granting legitimacy to diverse sense-making ontologies of medicine within a continuum of provider-patient meaning-making. Theoretically, CAM knowledge of holistic health integrates the experiential praxis of the patient’s spiritual and physiological self and the relational praxis of the patient’s biological-sociocultural-epigenetic relationships in the conceptualization and delivery of health outcomes. The study findings recommend including CAM knowledge discourses to inform the epistemological foundations of basic medicine. Pragmatically, the study recommends support for efforts to include credentialing of CAM practitioner teaching within allopathic healthcare institutions, faculty development within existing allopathic health professional schools, and incorporation of CAM content in allopathic medical education and practice.